A composite electrodeposited PbO2/SnO2 positive electrode material for hybrid supercapacitors. Issue 120 (19th November 2015) - Dan, Yuanyuan; Lin, Haibo; Chen, Lizhuang; Zhang, Li; Su, Jing; Yue, Huijuan; Cai, Xingwei
Abstract : PbO2 /SnO2 composites have been prepared by a composite electrodeposition method from Pb 2+ solution containing different amounts of suspended nano-SnO2 particles. Abstract : PbO2 /SnO2 composites have been prepared by a composite electrodeposition method from Pb 2+ solution containing different amounts of suspended nano-SnO2 particles. The chemical composition, crystal structure and surface morphology of the composites were characterized by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results indicate that the composite composed of rutile phase SnO2 and β-PbO2 is rough and porous. The R F of the PbO2 /SnO2 composite is approximately 10 times higher than that of the pure PbO2 electrode. The electrochemical behavior and the capacitance performance of the composite are determined by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and charge–discharge tests. The composite shows a high specific capacitance up to 208 F g −1, which is four times the specific capacitance of pure PbO2 and two times that of pure SnO2 .